Redesigning and Updating the Indiana State Department of Health Zoonotic and Vector-Borne Disease Website - Drakes, Crystal (My University, 2019)
In August 2017, I met with Dr. Jennifer Brown, the state public health veterinarian for Indiana, about completing a project that would fulfill the requirements for my MPH field experience. We collaborated on a project to redesign and provide up-to-date information on the Epidemiology Resource Center website of the Indiana State Department of Health (ISDH), specifically the Zoonotic and Vector-Borne Epidemiology/ Entomology pages. The entire website was redesigned. My responsibility included providing updated datasheets for the tick-borne and mosquito-borne disease pages. Once these sheets are completed, they would be reviewed by ISDH staff members also working on these webpages, and then be officially published on the website to be accessed by the public. The details of my involvement in this project for my field experience are detailed in this report.
Keywords: zoonoses; vector-borne diseases; tick-borne diseases; mosquito-born diseases; epidemiology